Intervensi dalam Pemeriksaan Sengketa Tata Usaha Negara - Mario Viano Rasi Wangge; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Warmadewa Press, 2021)
Judicial power is done by a Supreme Court and judicial bodies under it, including the State administrative court with two subjects or parties who are litigating in the PTUN, namely the defendant and the plaintiff. The purpose of this study is to reveal the system for examining interventions in state administration as well as arrangements for interventions in state administrative disputes. the type of research used is normative law with a statute approach. The source of data used is the secondary data. The technique of collecting legal materials used is by reading and quoting by analyzing the relevant laws and then the collection and collection of the literature materials are processed qualitatively. The result shows that there are several possible motivations for the entry of third parties in the judicial process, namely on their own initiative, at the request of the judge, and at the request of one of the parties (the presecutor/defendant) and the state administrative court regulate the entry method and motivation for the intervention of the party to enter the examination process. State Administrative Disputes.